Fault location method of wind turbine transmission chain system based on lumped parameter thermal network model - Shiyu Lin; Hongshan Zhao; Chengyan Sun; Weixin Yang; Xibei Li (International Journal of Electrical Power & Energy Systems)
Locking the location of the fault area accurately can effectively reduce the downtime. Therefore, a fault location method of wind turbine transmission chain system based on lumped parameter thermal network (LPTN) is proposed. Firstly, we analyzed the main heat generation forms and heat transfer paths based on the structure of transmission chain system. Secondly, the LPTN of transmission chain system is established. The heat generation power and thermal resistance of transmission chain system are calculated, and the solution formula of transient thermodynamic equation of node temperature is deduced. Thirdly, two fault location methods of wind turbine transmission chain system based on LPTN are proposed: (1) the method based on LPTN only, (2) the method considering the modification of operating conditions based on LPTN. Finally, 2 MW wind turbine data are used for experimental verification, and the results show that the maximum temperature residual of LPTN is less than 5℃. The fault location is verified by five kinds of transmission chain fault cases. The results show that the two methods can accurately locate the fault area. The research results can guide the fault maintenance of wind turbine, which is of great significance in reducing the downtime of wind turbine.